Transforming Tablet Production in Indonesia with 66% Faster Manufacturing: Mengubah Produksi Tablet di Indonesia dengan Manufaktur 66% Lebih Cepat - Yus’Ady, Tiva Hendra; Sulistiyowati, Wiwik (Universitas Muhammadiyah Sidoarjo, 2024)
This study addresses the high production costs of tablet products at PT. XYZ, a pharmaceutical company in Indonesia, due to long cycle and takt times. Using Causal Branching and KATA methods, data were collected over eight months through observations, interviews, and quantitative analysis. The study achieved a 43% reduction in reject foils from destripping, a 40% decrease in total cycle time, and a 66% reduction in takt time. These results highlight effective strategies for optimizing manufacturing processes and reducing costs in the pharmaceutical industry. Highlights: Cost Reduction: 43% reject foils, 40% cycle time reduction. Methodology: Used Causal Branching and KATA for problem-solving. Data Collection: Eight-month study with observations, interviews, quantitative analysis. Keywords: Tablet production, Cycle time reduction, Takt time optimization, Causal Branching, KATA method